Fatores relacionados à autopercepção da necessidade de tratamento odontológico entre idosos Factors associated to self perceived need of dental care among Brazilian elderly - Andréa Maria Eleutério de Barros Lima Martins; Sandhi Maria Barreto; Isabela Almeida Pordeus (Universidade de São Paulo, 2008)
OBJETIVO: Analisar fatores associados à autopercepção da necessidade de tratamento odontológico entre idosos. MÉTODOS: Foram pesquisados 5.326 indivíduos incluídos em amostra dos idosos (65-74 anos) brasileiros do inquérito domiciliar de saúde bucal realizado em 2002/2003 pelo Ministério da Saúde. A análise foi baseada no modelo de Gift, Atchison & Drury e foi utilizada a regressão de Poisson para análise de inquéritos com amostras complexas. RESULTADOS: Do total da amostra, 2.928 (55%) idosos relataram necessitar tratamento odontológico. A autopercepção dessa necessidade foi menor entre aqueles com 70 anos ou mais (RP=0,94; IC 95%: 0,89;0,99), que não receberam informações sobre como evitar problemas bucais (RP=0,89; IC 95%: 0,83;0,95) e que eram edentados (RP=0,68; IC 95%: 0,62;0,74). Foi maior entre aqueles que autoperceberam: saúde bucal regular (RP=1,31; IC 95%: 1,21;1,41) ou ruim/péssima (RP=1,29; IC 95%: 1,19;1,41); aparência como regular (RP=1,23; IC 95%: 1,15;1,32) ou ruim/péssima (RP=1,28; IC 95%:1,18;1,39); mastigação como regular (RP=1,08; IC 95%: 1,01;1,15) ou ruim péssima (RP=1,13; IC 95%:1,05;1,21); os que relataram dor nos dentes ou gengivas nos seis meses anteriores ao inquérito (RP=1,27; IC 95%: 1,18;1,36); os que necessitavam de prótese em uma arcada (RP=1,29; IC 95%: 1,19-1,39) ou em ambas (RP=1,27; IC 95%: 1,16;1,40). CONCLUSÕES: Informação, condições de saúde bucal e questões subjetivas estiveram associadas à autopercepção da necessidade de tratamento odontológico. Os resultados reforçam a necessidade de capacitar os indivíduos para realizarem o auto-exame bucal e identificar precocemente os sinais e sintomas não dolorosos das lesões da mucosa, da cárie e da doença periodontal. OBJECTIVE: To analyze factors associated with the self-perceived need for dental treatment among elderly people. METHODS: A total of 5,326 individuals who were included in a sample of Brazilian elderly people aged 65-74 years in a home survey on oral health conducted by the Brazilian Ministry of Health in 2002/2003 were investigated. The analysis was based on the model of Gift, Atchison & Drury, and Poisson regression for analysis of surveys with complex samples was used. RESULTS: Out of the whole sample, 2,928 (55%) of the elderly people said they needed dental treatment. This need was perceived less frequently among those aged 70 years or over (PR=0.94; 95% CI: 0.89;0.99), those who had not received information on how to avoid oral problems (PR=0.89; 95% CI: 0.83;0.95) and those who were edentate (PR=0.68; 95% CI: 0.62;0.74). The perceived need was greater among those who self;rated their oral health as regular (PR=1.31; 95% CI: 1.21;1.41) or poor/very poor (PR=1.29; 95% CI: 1.19;1.41), their appearance as regular (PR=1.23; 95% CI: 1.15;1.32) or poor/very poor (PR=1.28; 95% CI: 1.18;1.39) and their chewing as regular (PR=1.08; 95% CI: 1.01;1.15) or poor/very poor (PR=1.13; 95% CI: 1.05;1.21). It was also greater among those who reported pain in their teeth or gums over the six months prior to the survey (PR=1.27; 95% CI: 1.18;1.36) and among those who needed a prosthesis in one arch (PR=1.29; 95% CI: 1.19;1.39) or both (PR=1.27; 95% CI: 1.16;1.40). CONCLUSIONS: Information, oral health conditions and subjective questions were associated with self-perceived need for dental treatment. The results reinforce the need to capacitate individuals to carry out oral self-examination and identify non-painful signs and symptoms of mucosal lesions, caries and periodontal disease at an early stage.